Estimation volume of solid waste on new dumping area at Rimba Mas, Perlis / Mohd Badrul Hisham Ar Azmi - Ar Azmi, Mohd Badrul Hisham (2018)
The rapid development in the design, research and production of various types of Unmanned Aerial Vehicle has an influence on a wide range of application and fields. UAV offers the rapid data collection and can avoid hazardous environment without risk of human and others. This study is conducted to estimate volume of solid waste on new dumping area at Rimba Mas, Perlis and it can serve as an alternative to conventional technique use in this field. In this study, landfill aerial photographs were obtained using digital cameras attached to the UAV while altitude data were obtained from GPS observations. Data obtained are processed using several software to produce products such as orthophoto, contour map, DEM model, and calculation of solid waste volume contained in each cell in landfill. Each product is evaluated for precision assessment using the root mean square error (RMSE), error in pixel error, and error in image. In conclusion, this study has achieved all the proposed objectives and proves that the UAV system can be used for estimation of volume for solid waste products.